DYSTOPIA IN PUTU WIJAYA’S SHORT STORY PROTES - Hidayati, Hidayati; Anayati, Wan; Mayasari, Mayasari; Geubrina, Misla; Wardana, Muhammad Kiki (JOURNAL OF LANGUAGE, 2024)
Dystopia paints a grim portrayal of the future, spotlighting threats to individual freedom, human rights, and core human values. Putu Wijaya's short story Protes employs the dystopian concept to provoke critical examination of society's trajectory and to caution against the potential adverse outcomes of unsustainable policies or behaviors. This study adopts a literary sociology approach, an interdisciplinary method blending sociological principles with literary analysis to unravel the social significance embedded within the text. Supported by pertinent concepts and theories, the research employs qualitative methods, generating descriptive data from the written words of the short story Protes, which serve as the primary data source. The researchers themselves serve as the research instruments. Data collection employs a tabulation system structured around discussion points pertaining to dystopian aspects. Analysis involves thorough reading and comprehension of the text, selection and categorization of relevant data, identification of key problem areas, description of observations based on the data, compilation of a research report, and ultimately, drawing conclusions. The findings reveal that Protes encompasses dystopian elements manifested in the forms of poverty, social conflict, and environmental degradation.